The epigenetic paradigm in periodontitis pathogenesis - Vamsi Lavu; Vettriselvi Venkatesan; Suresh Ranga Rao (Wolters Kluwer Medknow Publications, 2015)
Epigenome refers to "epi" meaning outside the "genome." Epigenetics is the field of study of the epigenome. Epigenetic modifications include changes in the promoter CpG Islands, modifications of histone protein structure, posttranslational repression by micro-RNA which contributes to the alteration of gene expression. Epigenetics provides an understanding of the role of gene-environment interactions on disease phenotype especially in complex multifactorial diseases. Periodontitis is a chronic inflammatory disorder that affects the supporting structures of the tooth. The role of the genome (in terms of genetic polymorphisms) in periodontitis pathogenesis has been examined in numerous studies, and chronic periodontitis has been established as a polygenic disorder. The potential role of epigenetic modifications in the various facets of pathogenesis of periodontitis is discussed in this paper based on the available literature.